Polarizable Additive with Intermediate Chelation Strength for Stable Aqueous Zinc-Ion Batteries - Xia, Yuting; Tong, Rongao; Zhang, Jingxi; Xu, Mingjie; Shao, Gang; Wang, Hailong; Dong, Yanhao; Wang, Chang‑An (Nano-Micro Letters, 2024)
Aqueous zinc-ion batteries are promising due to inherent safety, low cost, low toxicity, and high volumetric capacity. However, issues of dendrites and side reactions between zinc metal anode and the electrolyte need to be solved for extended storage and cycle life. Here, we proposed that an electrolyte additive with an intermediate chelation strength of zinc ion—strong enough to exclude water molecules from the zinc metal-electrolyte interface and not too strong to cause a significant energy barrier for zinc ion dissociation—can benefit the electrochemical stability by suppressing hydrogen evolution reaction, overpotential growth, and dendrite formation. Penta-sodium diethylene-triaminepentaacetic acid salt was selected for such a purpose. It has a suitable chelating ability in aqueous solutions to adjust solvation sheath and can be readily polarized under electrical loading conditions to further improve the passivation. Zn||Zn symmetric cells can be stably operated over 3500 h at 1 mA cm−2. Zn||NH4V4O10 full cells with the additive show great cycling stability with 84.6% capacity retention after 500 cycles at 1 A g−1. Since the additive not only reduces H2 evolution and corrosion but also modifies Zn2+ diffusion and deposition, highlyreversible Zn electrodes can be achieved as verified by the experimental results. Our work offers a practical approach to the logical design of reliable electrolytes for high-performance aqueous batteries. Highlights: 1 Design principle of a reliable electrolyte based on chelation strength is proposed for high-performance aqueous batteries. 2 The addition of penta-sodium diethylene-triaminepentaacetic acid salt is effective in dynamically modulating anode/electrolyte interface, inhibiting water-related side reactions, and mitigating dendrite generation on zinc anodes. 3 Symmetrical, Zn||Cu half and Zn||NH4V4O10 full cells using the new electrolyte exhibit improved electrochemical performance.